Setting the task of automating the method of designing the longitudinal profile of engineering networks (Международный научный журнал «Инженер», 2026)
The article considers the task of automating the construction of a longitudinal profile of engineering watersupply networks. A technique based on the use of geometric data of the pipeline route and hydrauliccalculations is proposed. The software architecture includes modules for input of initial data, calculationof profile parameters and visualization of results. As part of the study, a program code was implementedthat was used to perform a hydraulic calculation of the engineering network. The calculation of pressurelosses is carried out using basic hydraulic formulas such as the Darcy–Weisbach equation. As an example,the calculation results for a typical water supply system are shown, demonstrated by a graph of pressureloss changes along the route of the water supply network. The developed software package simplifies andspeeds up the calculations, which is confirmed by the analysis of the results.